Demand and supply effects and returns to college education: Evidence from a natural experiment with engineers in Denmark - Hans-Peter Y. Qvist; Anders Holm; Martin D. Munk (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2016)
The demand and supply model predicts that a larger relative net supply of a particular skill group will negatively affect its relative wage. To test this, we use the opening of a new university in Denmark as a natural experiment. We show that the opening of Aalborg University created a shock to the supply of structural engineers in the mid-1980s. Because Aalborg University did not have a chemical engineering program, we use chemical engineers as a control group and find that the wages of structural engineers dropped in and around 1984, when the supply of structural engineers peaked.
Keywords: 330